Does the time to diagnosis and treatment influence outcome in adults with pleural infections - Mads Brögger Klausen; Christian Laursen; Morten Bendixen; Babu Naidu; Eihab O Bedawi; Najib. M. Rahman; Thomas Decker Christensen (European Clinical Respiratory Journal, 2023)
ABSTRACTObjective To investigate the effect of early diagnosis and intervention in adult patients with complicated parapneumonic pleural effusion or pleural empyema and the impact on outcomes.Methods A systematic review based on a literature search of the PubMed database was performed.Results Eleven eligible studies were included; nine observational studies and two randomised controlled trials totalling a study population of 10,717 patients. The studies were conducted from 1992 to 2018, all in Europe and Northern America except one. Results varied between studies, but a trend towards better outcome in patients with shorter duration of symptoms and quicker initiation of treatment was found. We found that duration of symptoms before treatment may affect length of hospital stay, rate of conversion to open surgery, and frequency of complications.Conclusion We found that an earlier intervention in adults suffering from complicated parapneumonic pleural effusion and pleural empyema may potentially improve the outcome of patients in terms of length of stay, conversion to open surgery, and general complications following treatment, but not regarding mortality. Further studies are required to specify the timing of each intervention, and direct comparison in early management of interventions.